Taxpayer Awareness, Application Of Electronic Systems, And Understanding Of Taxpayers’ Compliance With Tax Laws And Regulations Regarding Their Risk Appetite Level As Moderating Variables - Kasim Sinen; Zainuddin Zainuddin (Bongaya Journal for Research in Accounting (BJRA), 2021)
This research is a quantitative study which aims to examine the effect of taxpayer awareness, e-system application and understanding of tax regulations on the level of taxpayer compliance with risk preference as the moderating variable. The number of samples studied in this study were 115 samples. The data in this study are primary data in the form of respondents' answers distributed to individual taxpayers who are registered at (KPP) Pratama Ternate who make payments at KPP Pratama Ternate. All data obtained were processed using SPSS 16 for windows with multiple linear regression analysis. Based on the research results, the application of e-systems and understanding of tax regulations affects the level of taxpayer compliance. Meanwhile, taxpayer awareness has no effect on the level of taxpayer compliance. Risk preference is able to moderate the effect of understanding tax regulations on the level of taxpayer compliance. Risk preference is not able to moderate the effect of taxpayer awareness and the application of e-system on the level of taxpayer compliance.